Characterizing Toolkits for Platform Independent Chatbot Development - Leifheit, Bhruno Roan; Basso, Fábio Paulo; Silva, Williamson (Anais do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2023: Anais do XIX Simpósio Brasileiro de Sistemas de Informação, 2023)
Context: With the increase in the use of conversational agents, especially those based on written language (chatbots), users can interact with machines through natural language. Problem: The growing demand for chatbots has raised problems in building and deploying these conversational agents to different platforms, implying adaptation costs. Solution: We performed a systematic grey literature review to identify a set of DSL-supported tools for platform-independent chatbot development. IS Theory: Not applicable. Method: This research sought to list tools and DSLs for developing platform-independent chatbots, carried out through a review of the grey literature, addressing a qualitative analysis of primary studies. Summary of Results: After conducting the studies, we discovered 14 tools and 10 DSLs supporting the construction of platform-independent chatbots. Contributions and Impact in the IS area: A characterization of tools and DSLs in state of the art supporting the construction of platform-independent chatbots.